Response to Vaccination in Infants Exposed to Antitumor Necrosis Factor Alpha In Utero. Issue 10 (13th July 2021) - Wieringa, Jantien W.; van Beek, Ron H. T.; Rövekamp, Lyanne W.; Driessen, Gertjan J. A.; van Wering, Herbert M.
Abstract : Supplemental Digital Content is available in the text. Abstract : In this retrospective cohort study, the response to routinely administered Haemophilus influenzae type B vaccine, pneumococcal and pertussis vaccinations in 27 children exposed to antitumor necrosis factor alpha (anti-TNFα) during pregnancy was measured. The overall vaccination response seems comparable for children exposed to anti-TNFα and healthy infants. After primary vaccination series, inadequate response was present in some patients and might be related to exposure to anti-TNFα.